Розвиток документознавства в умовах новітніх викликів часу - Бездрабко, Валентина (Видавництво Львівської політехніки, 2016)
The modern concepts of documentary studies development represented in the works prominent researchers have been analyzed. The peculiar, different and common approaches interpreting of the content of documentary science, development prospects have been highlighted.
Keywords: документознавство; документ; інформація; соціальні комунікації; інформаційні науки; наука